BL‐11C Micro‐MX: a high‐flux microfocus macromolecular‐crystallography beamline for micrometre‐sized protein crystals at Pohang Light Source II. (2nd June 2021) - Gu, Do-Heon; Eo, Cheolsoo; Hwangbo, Seung-A; Ha, Sung-Chul; Kim, Jin Hong; Kim, Hyoyun; Lee, Chae-Soon; Seo, In Deuk; Yun, Young Duck; Lee, Woulwoo; Choi, Hyeongju; Kim, Jangwoo; et al.
Abstract : A new protein crystallography beamline (BL‐11C) has been constructed at Pohang Light Source II. The BL‐11C beamline allows routine protein‐structure determinations under a robot sample‐mounting system and room‐temperature structure determinations through synchrotron serial crystallography experiments. Abstract : BL‐11C, a new protein crystallography beamline, is an in‐vacuum undulator‐based microfocus beamline used for macromolecular crystallography at the Pohang Accelerator Laboratory and it was made available to users in June 2017. The beamline is energy tunable in the range 5.0–20 keV to support conventional single‐ and multi‐wavelength anomalous‐dispersion experiments against a wide range of heavy metals. At the standard working energy of 12.659 keV, the monochromated beam is focused to 4.1 µm (V) × 8.5 µm (H) full width at half‐maximum at the sample position and the measured photon flux is 1.3 × 10 12  photons s −1 . The experimental station is equipped with a Pilatus3 6M detector, a micro‐diffractometer (MD2S) incorporating a multi‐axis goniometer, and a robotic sample exchanger (CATS) with a dewar capacity of 90 samples. This beamline is suitable for structural determination of weakly diffracting crystalline substances, such as biomaterials, including protein, nucleic acids and their complexes. In addition, serial crystallography experiments for determining crystal structures at room temperature are possible. Herein, the current beamline characteristics, technical information for users and some recent scientific highlights are described.